Upaya Pemerintah Indonesia Memaksimalkan CSR dalam Pemberdayaan Perempuan : Refleksi dari Negara Islandia - Fanny Yolan Tamba (Indonesian Accounting Research Journal, 2025)
Gender inequality remains a global concern as women often lack equal opportunities in workforce participation compared to men. This disparity arises from factors such as limited access to education, health services, and suitable job opportunities, as well as broader social constraints. Addressing this issue requires structured efforts, one of which is through the implementation of Corporate Sustainability Reports (CSR) that integrate gender equality into business practices. Using a scoping review method, this research maps the relationship between women’s work participation and empowerment by analyzing the gender gap, reviewing government efforts in maximizing CSR, and adopting innovations from other countries. Iceland, recognized as the world’s leader in gender equality, serves as a benchmark for best practices. The findings are expected to guide policymakers in evaluating sustainable financial reporting regulations, emphasizing CSR’s role in advancing women’s empowerment to foster an inclusive and sustainable economy.